2014
DOI: 10.1016/j.ypmed.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' beliefs about effectiveness of cancer screening tests: A national survey of family physicians, general internists, and obstetrician–gynecologists

Abstract: Objective To study physicians' beliefs about the effectiveness of different tests for cancer screening. Methods Data were examined from the Women's Health Survey of 1574 Family Medicine, Internal Medicine, and Obstetrics–Gynecology physicians to questions about their level of agreement about the clinical effectiveness of different tests for breast, cervical, ovarian, and colorectal cancer screening among average risk women. Data were weighted to the U.S. physician population based on the American Medical Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…In two articles [ 28 , 30 ], physician participants were asked to rate the influence of the USPSTF guidelines, and in two others [ 33 , 34 ], these physicians rated their level of trust in different organizations including the USPSTF. Physicians were also asked about the CTFPHC in two articles [ 26 , 27 ], and this guideline was cited in one other article [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two articles [ 28 , 30 ], physician participants were asked to rate the influence of the USPSTF guidelines, and in two others [ 33 , 34 ], these physicians rated their level of trust in different organizations including the USPSTF. Physicians were also asked about the CTFPHC in two articles [ 26 , 27 ], and this guideline was cited in one other article [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Physicians were also asked about the CTFPHC in two articles [ 26 , 27 ], and this guideline was cited in one other article [ 29 ]. Moreover, the five American studies [ 28 , 30 , 32 34 ] made reference to PCPs’ sub-specialties’ guidelines, so mammography recommendations for the American College of Obstetricians and Gynecologists (ACOC), the American Academy of Family Physicians (AAFP), and the American College of Physicians (ACP) are listed. The two North American task force organizations currently recommend routine screening in average-risk women between the ages of 50 and 74.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a survey of internal medicine (IM), family medicine (FM) and gynecology (GYN) physicians found that physicians in these specialties are more likely to recommend screening initiation at age 40 (65% IM, 64% FM, 92% GYN) than age 50 (Corbelli et al 2014). And a 2014 survey of physicians found that 50.6% of physicians “strongly agree” and 44% of physicians “agree” that mammography screening is “effective” for women ages 40–49 (Miller et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…911 However, identifying women who need cervical cancer screening is often challenging, and both overscreening and underscreening occur. 1214 Referrals to another institution for cervical cancer screening can result in loss to follow-up. 15 Furthermore, timely follow-up and treatment are required for screening to be effective, and racial, socioeconomic, and other disparities occur.…”
mentioning
confidence: 99%